Bazedoxifene for HRT?. Issue 4 (13th April 2017) - Unknown
Abstract : Duavive (Pfizer) is a modified-release formulation of conjugated oestrogens plus bazedoxifene acetate (a selective oestrogen receptor modulator). It is licensed for treatment of oestrogen deficiency symptoms in postmenopausal women with a uterus for whom treatment with progestogen-containing therapy is not appropriate. 1, 2 It was licensed by the European Medicines Agency (EMA) in 2014 and launched in the UK in July 2016. 1, 3 Here, we review the evidence on efficacy and safety of conjugated oestrogens/bazedoxifene and consider its place in the management of symptoms associated with the menopause.